Assessment of rTMS treatment effects for methamphetamine use disorder based on EEG microstates - Li, Yongcong; Yang, Banghua; Ma, Jun; Gao, Shouwei; Zeng, Hui; Wang, Wen (Behavioural brain research, 2024)
Microstates have been proposed as topographical maps representing large-scale resting-state networks and have recently been suggested as markers for methamphetamine use disorder (MUD). However, it is unknown whether and how they change after repetitive transcranial magnetic stimulation (rTMS) intervention. This study included a comprehensive subject population to investigate the effect of rTMS on MUD microstates. 34 patients with MUD underwent a 4-week randomized, double-blind rTMS intervention (active=17, sham=17). Two resting-state EEG recordings and VAS evaluations were conducted before and after the intervention period. Additionally, 17 healthy individuals were included as baseline controls. The modified k-means clustering method was used to calculate four microstates (MS-A∼MS-D) of EEG, and the FC network was also analyzed. The differences in microstate indicators between groups and within groups were compared. The durations of MS-A and MS-B microstates in patients with MUD were significantly lower than that in HC but showed significant improvements after rTMS intervention. Changes in microstate indicators were found to be significantly correlated with changes in craving level. Furthermore, selective modulation of the resting-state network by rTMS was observed in the FC network. The findings indicate that changes in microstates in patients with MUD are associated with craving level improvement following rTMS, suggesting they may serve as valuable evaluation markers. •The durations of MS-A and MS-B in MUD were significantly lower than that in HC, but increased after rTMS.•The changes in microstate indicators were found to be significantly correlated with changes in clinical VAS scores.•The functional connectivity analysis of homologous EEG assisted in confirming the positive effect of rTMS.